Analysis of Arabic Language Learning Needs in Vocational High Schools Based on the Independent Curriculum - Khadori, Khambali; Mohammad Sarip; Andri Ilham (Prodi Pendidikan Bahasa Arab Sekolah Tinggi Agama Islam As-Sunnah, 2025)
This study aims to determine the needs of vocational high school students for Arabic language learning in the Merdeka Curriculum based on deep learning as a basis for compiling relevant textbooks. The method used is a descriptive quantitative approach by distributing needs analysis questionnaires to 474 students from three public vocational high schools in DKI Jakarta. The results of the study concluded that 1) 84.3% of students have basic Arabic reading skills, however, 84.4% want transliteration and Latin reading; 2) 92.4% want grammar material and 93.8% want proficiency material presented on themes in the home, classroom, and school environment; 3) 79% of the material is presented in the form of textbooks and 56.7% online systems that direct visual, auditory, and kinesthetic learning tendencies. This study provides an initial contribution in the form of data on the real needs of vocational high school students that can be used to design more applicable and student-centered teaching materials, namely contextual, communicative, and flexible learning in accordance with the characteristics of the Merdeka Curriculum.